New records of three Basidiomycetous species from Iraq using phenotypic and phylogenetic analyses - Sara Q. Sulaiman; Rajaa Abdulrazzaq Al Anbagi; Fakhir R. H. Alshuwaili; Sh. Abdalrahman, Adiba (Plant Science Today, 2024)
Wild macrofungi have potential functions in ecosystems and sustainable developments through their roles in waste management, human health and societal upliftment. However, there is limited knowledge of wild macrofungi in Iraq. Three interesting collections within Chlorophyllum, Mycenastrum and Ossicaulis genera related to basidiomycetes were discovered in central and northeastern parts of Iraq in 2022 during a field investigation on wild macrofungi. Molecular identification and morphological characterization were carried out for these collections. The molecular phylogenetic and phenotypic analyses confirmed that isolates are related to three species within two families )Agaricaceae and Lyophyllaceae) belonging to the order Agaricales and class Agaricomycetes. Based on the current publications, these species were the first records from Iraq. Chlorophyllum agaricoides, Mycenastrum corium and Ossicaulis salomii sequences were submitted as the first sequences from Iraq into the international biological database GenBank. The molecular phylogenetic tree formed three independent lineages in each genus with high support. The introduced species can easily be separated from closely related species in an evolutionary framework. The study's results might aid in further investigations into the macrofungi in Iraq.